Model tests of the raw-water pipeline under the excessive stacking load - Wang, Jun; Wang, Lei; Chen, Qingyang; Shi, Liang; Zhou, Jun (Frontiers in Earth Science, 2023)
To investigate the effect of excessive stacking loadings on the deformation of raw-water pipelines, a model test was designed based on the analogous theory in this paper. The design of the model box, selection of pipeline material, and preparation of remolded soil were conducted, respectively. A theoretical formula was derived to convert the results of the model test into actual ones. Then, the field test data and three-dimensional numerical values were employed to verify the correctness of the model test results. Finally, the stresses of pipelines were discussed under different loading conditions, pipe diameters, buried depths, and compactness of underlying soils, and the guidelines for pipeline protection were proposed based on the results of the model tests. It can lay a solid theoretical and practical foundation for the protection of buried pipelines.